Clinical predictors and RT-PCR profile of prolonged viral shedding in patients with SARS-CoV-2 Omicron variant in Shanghai: A retrospective observational study - Zhang, Wen; Zhou, Shuang; Wang, Gang; Cao, Min; Sun, Ding; Lu, Wei; Shi, Li; Guo, Yong; Xu, Xiangru; Pu, Yuting; Chen, Caiyu; Yang, Hongqiang; et al. (Frontiers in Public Health, 2022)
Objective To evaluate determinants of prolonged viral RNA shedding in hospitalized patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant infection. Materials and methods Hospitalized patients tested SARS-CoV-2 positive by nasopharyngeal real-time reverse transcriptase-polymerase chain reaction (RT-PCR) were included in the single-center, retrospective study. Patients were divided into 2 groups according to the timing of viral clearance (≤ 8 days, “early clearance” and ≥15 days, “late clearance”). Results 4,084 patients were included in the study (1,023 late clearance, 3,061 early clearance), with median age of 50 years and a higher proportion (61.4%) of male. Univariate analyses showed that comorbidities (including hypertension, diabetes, and coronary heart disease), receiving vaccine, the number of vaccinations, cycle threshold (Ct) open reading frame 1ab (ORF 1ab), and nucleocapsid protein (N) gene values on admission were associated with late viral clearance. In the multivariable analysis, the number of vaccinations (P = 0.010) and Ct ORF 1ab gene (P < 0.001) values on admission were significantly associated with late viral clearance. Generalized Estimating Equations (GEE) analysis showed that the Ct value of ORF 1ab gene and N gene remained unchanged within 3 days, and showed progressively higher values with increasing days during late viral RNA clearance. Conclusion The number of vaccinations and Ct values of ORF 1ab gene were independently associated with a prolonged SARS-CoV-2 RNA shedding.